Alvartlk impact exercises in the development of the rated speed and its relationship Balthdev of the football players of the junior ages (14-16 years) - Hamidullah, Ahmed (Journal of Physical Education, 2011)
Impact exercises Alvartlk legalized in the development of speed and their relationship struck first for soccer players ages (14-16) years. The research aims to identify the impact of exercise Alvartlk trophy in the development of speed and their relationship struck first for the football players. The sample consists of (20) players from the Youth Sports Club Freedom ages (14-16) years old) football. Were selected randomly, the way the lottery and divided into two groups, the officer and pilot, and by (10) players per group. Was applied to the curriculum prepared by the trainer to the control group, while the application of the curriculum prepared by the researcher for the experimental group. of the search Introduction to the research and its importance Is the game of football most sports the world’s known that I took a spread widening gradually, with the growing interest by learning and developing as a popular sport in the world, to enjoy this game of suspense and excitement and fun for the viewers and practitioners alike, as this game has become first because of the ease and practiced being a global game attracts millions of people of different ages and groups through all media space